IEEE AP-S Digital Archive : 2003 (IEEE Antennas and Propagation Society ; Parity Computing)
Base de datos de publicaciones de la Antennas and Propagation Society que da acceso por autor, temática e índices de las revistas, así como resúmenes, a los artículos en PDF de: Transactions on Antennas and Propagation (2001-2003), Antennas and Propagation Magazine (2001-2003), Antennas and Wireless Propagation Letters (2002-2003) y Antennas and Propagation Symposium Digests (2001-2003). Para ediciones anteriores al 2001 no incluye el texto, pero sí permite la búsqueda por autor, temática, índices y resumen de: Transactions on Antennas and Propagation (1952-2000); Antennas and Propagation Magazine (1990-2000); Antennas and Propagation Newsletter (1958-1989); Antennas and Propagation Symposium Digests (1963-2000); Convention Record: Antennas and Propagation (1953-1966), WESCON Convention Record: Antennas and Propagation (1957-1960).